Survey of psychological disturbance in patients attending a sexually transmitted diseases clinic. Issue 2 (April 1986) - Fitzpatrick, R; Frost, D; Ikkos, G
Abstract : A survey of psychological disturbance was conducted in a sexually transmitted disease (STD) clinic, using the general health questionnaire, the Crown-Crisp experiential index, and the illness concern questionnaire. Of 381 patients who completed the questionnaire, 158 (43%) had general health questionnaire scores indicating that they were psychiatric cases. Psychological disturbance was more common in women. The association between general health questionnaire caseness and patients' reports of concerns and worries about illness in relation to their presenting complaint was significant. The Crown-Crisp experiential index scores of cases were lower than those characteristic of patients attending psychiatric clinics, and much of the psychological disturbance found by this and other surveys of STD clinics may therefore represent distress in relation to the presenting problem. Of the 381 patients, 14 (4%) appeared to have an abnormal or unwarranted level of distress in relation to their presenting complaint.